Handcuffs to Education of Gender Minorities: The Impact of Educational Barriers on Labor Supply of the Transgender Community in Sri Lanka - Wijayawardhana, W. M. P. M.; Chaminda, J. W. D.; Siriwardhane, D. R. J. (My University, 2023)
This research study is to fill a research gap\ through an in-depth- qualitative study which explore causes for transgender under-education in Sri Lanka at the initial phase and investigate the impact of those causes on labor force engagements at the later stage. This is a qualitative study which use snowball sampling technique to select a working-age transgender sample of 25 participants. In-Depth Interview method was used as the dominant data collection method along with observations, field notes and web/digital contents. Early-age school leaving, Academic career delays due to gender transition process, School culture of aggression, Unsheltered homelessness of transgender children, Social isolation, Educational personality loss, and the problem of access to tertiary education are recognized as the key causes for under-education observed among transgender community in Sri Lanka. Moreover, this study identified the impacts of under-education on Sri Lanka’s transgender labor supply too.
Keywords: Gender minorities teacher-student rapport social behavior educational right protection